ANALISIS PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF DAN LINGKUNGAN KERJA TERHADAP EFEKTIVITAS PENGAMBILAN KEPUTUSAN MANAJER: Studi pada Perusahaan Manufaktur di Kabupaten Lamongan - Ahmad Fathur Rozi; Rifky Ardhana Kisno Saputra; Estri Purwani Rahayu (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2025)
The purpose of this study was to analyze the influence of participative leadership style and work environment, both partially and simultaneously, on the effectiveness of managerial decision-making in manufacturing companies in Lamongan Regency. The research method used was quantitative with an explanatory approach. The study population consisted of 250 managers from 45 manufacturing companies, with a sample of 170 respondents selected through proportional random sampling techniques. Data were collected using a closed questionnaire with a Likert scale of 1-5 which has been tested to be valid and reliable (Cronbach's Alpha > 0.70). Data analysis used multiple linear regression with classical assumption tests. The results of the study proved that: (1) Participative leadership style has a positive and significant effect on the effectiveness of decision-making (β = 0.428; p = 0.000); (2) Work environment has a positive and significant effect on the effectiveness of decision-making (β = 0.392; p = 0.000); (3) Simultaneously, both variables have a significant effect with a calculated F value of 45.892 (p = 0.000). The Adjusted R Square value of 0.609 indicates that 60.9% of the variation in decision-making effectiveness can be explained by these two independent variables. The study's conclusions confirm that the effectiveness of managerial decision-making in a Lamongan manufacturing company is significantly influenced by the implementation of a participatory leadership style and the quality of the work environment. The practical implications of these findings emphasize the importance of developing participatory leadership training programs and continuously improving the work environment to enhance the quality of managerial decision-making.